Optimization of Digitization-Based Ant Sugar Micro, Small and Medium Enterprises (UMKM) in Cimarias Village - Putra, Hendri Darma; Chandra Wijaya; Ishak Abdul Rojak; Muhammad Irfan Febrianto; Siti Maspupah; Rika Amalia (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Angkeub Hamlet, located in Cimarias Village, Pamulihan Subdistrict, Sumedang Regency, has great UMKM potential in palm sugar production. However, Angkeub Hamlet has challenges in developing its economy, namely the lack of community understanding of digital business. This research aims to open the insights of training participants about product diversification from palm sugar. This activity was carried out with a qualitative method in the form of direct discussions with residents, namely palm sugar craftsmen. The results of this thematic KKN program are that the community gained a new understanding of palm sugar cultivation, bookkeeping, product legality, and the operation of platforms for digital marketing through social media and e-commerce, and became a fostered village of Universitas Islam Nusantara. The conclusion of this program has contributed to the livelihood of the community by providing them with new income opportunities. Increased added value of printed palm sugar products into ant sugar. After participating in this program, the craftsmen can technically know the process of making ant sugar and digital marketing, but assistance is still needed to escort them to the production scale and legality. Therefore, the prospect of long-term cooperation output is in the form of an Islamic Nusantara University Assisted Village.